Propagation of SH waves in an regular non homogeneous monoclinic crustal layer lying over a non- homogeneous semi-infinite medium - Sethi, Madhu; Sharma, Anupam Deep (Zielona Góra: Uniwersytet Zielonogórski)
The present paper discusses the dispersion equation for SH waves in a non-homogeneous monoclinic layer over a semi infinite isotropic medium. The wave velocity equation has been obtained. In the isotropic case, when non-homogeneity is absent, the dispersion equation reduces to the standard SH wave equation. The dispersion curves are depicted by means of graphs for different values of non-homogeneity parameters for the layer and semi-infinite medium.
Keywords: SH waves; monoclinic; non homogeneity; differential equations